The Pedagogic Project as Provocative of the Collective Work in the School - Elaine Sampaio Araujo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The objective of this article is to discuss, starting from the historical-cultural perspective, the sense of a pedagogic project considering its procedural nature, the convergence of the personal and collective dimensions and the educational purpose. The goal is to notice the project as possibility in the field pragmatic and in the theory of the sciences of human formation, linking the human development with the schools and its projects. For that, it tries to demonstrate that pedagogic projects configured as activity don't just legitimate the collective participation as it establish a new theoretical and/or methodological order in the organization of the pedagogic work, provoking a school that learns and grows in the search of forming men and women of the best human quality.